Evaluation of Some Natural Zeolites and Their Relevant Synthetic Types as Sorbents for Removal of Arsenic from Drinking Water - R Menhage-Bena; H Kazemian; M Ghazi-Khansari; M Hosseini; SJ Shahtaheri (Tehran University of Medical Sciences, 2004)
The purpose of this study was to find a relatively inexpensive method for removal of arsenate and arsenite from drinking water. The capability of Iranian natural clinoptilolites, relevant synthetic zeolites A and P and Iron(П) modified of them was investigated for the uptake of arsenic anions from drinking water. Data obtained from ion-exchange using batch (static) technique showed that among the investigated zeolites, modified synthetic zeolite A was the most selective sorbent for removal of arsenic. In this study, the influence of factores including temperature, arsenic concentration, pH and zeolite particle size on removal of arsenic species from water was also determined and studied.